2018
DOI: 10.17576/pengurusan-2018-54-07
|View full text |Cite
|
Sign up to set email alerts
|

The Impact of Customer Value Co-Creation and Relationship Quality on Relationship Equity: Personality Traits as a Moderator

Abstract: This study aimed to examine the relationship among customer value co-creation, relationship quality, and relationship equity in the tailoring services in Malaysia. Moreover, this study also investigated whether customer personality trait plays a moderating role in the relationship of value co-creation behavior and relationship quality as well as the relationship between relationship quality and relationship equity. A total of 245 questionnaires were collected via purposive sampling from customers seeking tailo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
23
0
2

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 14 publications
(26 citation statements)
references
References 72 publications
1
23
0
2
Order By: Relevance
“…The prior literature indicates that firms with international quality certification (IQC) have a tendency to be more innovative than those who do not have it (Omar et al, 2020). The importance of quality certification standards in improving business performance, providing a framework for cost savings, increasing customer satisfaction, and facilitating firms' access to new markets cannot be overstated (Albulescu et al, 2016).…”
Section: International Quality Certification and Firm Innovationmentioning
confidence: 99%
See 1 more Smart Citation
“…The prior literature indicates that firms with international quality certification (IQC) have a tendency to be more innovative than those who do not have it (Omar et al, 2020). The importance of quality certification standards in improving business performance, providing a framework for cost savings, increasing customer satisfaction, and facilitating firms' access to new markets cannot be overstated (Albulescu et al, 2016).…”
Section: International Quality Certification and Firm Innovationmentioning
confidence: 99%
“…ISO 9001 is an international certification standard given to firms that have adopted a number of quality management principles, including a focus on customer, innovation and process approaches and continual improvement that aims to improve quality products and processes (Latan et al, 2020). The prior literature indicates that firms with international quality certification (IQC) have a tendency to be more innovative than those who do not have it (Omar et al, 2020). The importance of quality certification standards in improving business performance, providing a framework for cost savings, increasing customer satisfaction, and facilitating firms' access to new markets cannot be overstated (Albulescu et al, 2016).…”
Section: Theoretical Background and Hypothesis Developmentmentioning
confidence: 99%
“…Value co-creation from positive relationships, continuing negotiation, and equal status (Prahalad & Ramaswamy, 2004) would improve student-university relations. Co-creation of consumer value has a statistically significant effect on the consistency of relationships, satisfaction, and trust (Omar et al, 2018). Many scholars (e.g., Chen & Myagmarsuren, 2011) have shown that a high level of relationship quality increases loyalty (Omar et al, 2018).…”
Section: Relationship (Co2_3)mentioning
confidence: 99%
“…Co-creation of consumer value has a statistically significant effect on the consistency of relationships, satisfaction, and trust (Omar et al, 2018). Many scholars (e.g., Chen & Myagmarsuren, 2011) have shown that a high level of relationship quality increases loyalty (Omar et al, 2018). Thus, it can determine value-in-use significantly.…”
Section: Relationship (Co2_3)mentioning
confidence: 99%
“…Scholars argue that intra-sector differences are explained by the path-dependent and iterative nature of innovation process (Mahdi, 2002) and that, innovation is a non-linear dynamic system consisting of a cycle of divergent and convergent activities that may be repeated over time and at different organizational levels (Van de Ven et al, 2007). Previous SMEs' IT-based innovation adoption studies predominantly focused on adoption drivers and inhibitors (Eze et al, 2018c;Eze et al, 2018a;Omar et al, 2020;Busagara et al, 2020); industry culture; business process change (Poba-Nzaou et al, 2012); and organizational motivations (Trudel et al, 2012;Son and Benbasat, 2007) without so much recourse to information behaviour with regards to EICT adoption from a multidimensional perspective.…”
mentioning
confidence: 99%